2020
DOI: 10.1101/2020.04.23.058701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The conservation of a core virome inAedesmosquitoes across different developmental stages and continents

Abstract: 32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…Although viruses belonging to Sobemovirus genus and Luteoviridae family are known plant viruses and are of monopartite genome, Sobemo-like virus members have bi-segmented genomes and have been isolated primarily from insects [1,26]. It has been speculated that this group of viruses should be proposed as a new family [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although viruses belonging to Sobemovirus genus and Luteoviridae family are known plant viruses and are of monopartite genome, Sobemo-like virus members have bi-segmented genomes and have been isolated primarily from insects [1,26]. It has been speculated that this group of viruses should be proposed as a new family [32].…”
Section: Discussionmentioning
confidence: 99%
“…The number of newly discovered arthropod viruses has been exponentially increasing after the development of massive parallel sequencing technologies, but in the majority of the cases, little is known about their biology and ecology as well as their impact on human health and economy [ 24 , 25 ]. It was recently shown that insects host stable populations of viruses, or core viromes, that are vertically transmitted both in laboratory colonies and in nature [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The term "core virome" was recently coined to describe the set of ISVs common to the majority of individuals in a mosquito population (Shi et al 2019). The term has since been divided into two categories: vertical (passed from mother to offspring) and environmental (acquired from the environment) (Shi et al 2020). To date, research on Aedes mosquitoes suggests that at the population level core viromes are maintained across developmental stages (Shi et al 2020) and over short time scales (~ 1 year) (Boyles et al 2020, Shi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The term has since been divided into two categories: vertical (passed from mother to offspring) and environmental (acquired from the environment) (Shi et al 2020). To date, research on Aedes mosquitoes suggests that at the population level core viromes are maintained across developmental stages (Shi et al 2020) and over short time scales (~ 1 year) (Boyles et al 2020, Shi et al 2020). However, it is unknown how well vertical core viromes are sustained over longer periods of time, or the degree to which environmental core viromes are transient.…”
Section: Introductionmentioning
confidence: 99%